Asymmetric Non-Commodity Output Responses to Commodity Price Shocks - Mati, Amine (IMF Working Papers; Working Paper, 2021)
This paper focuses on identifying potential asymmetric responses of non-commodity output growth in times of positive and negative commodity terms-of-trade shocks. Using a sample of 27 oil-exporting countries and a panel VAR method, the study finds: 1) the short-and medium-run response of real non-commodity GDP growth is larger for negative shocks than positive shocks; 2) this asymmetry is more pronounced in countries with weak pre-existing fundamentals-high levels of public debt and low levels of international reserves-which also serve to amplify the volatility of the response; 3) the output response to positive shocks is stronger following a sustained period of CTOT increases, while the impact of negative shocks on output are more damaging when they occur after a period of CTOT decline.